Plasma cystatin C as a marker for estimated glomerular filtration rate assessment in HIV-1-infected patients treated with dolutegravir-based ART. (24th April 2018) - Palich, Romain; Tubiana, Roland; Abdi, Besma; Mestari, Fouzi; Guiguet, Marguerite; Imbert-Bismut, Françoise; Katlama, Christine; Bonnefont–Rousselot, Dominique; Isnard-Bagnis, Corinne
Abstract: Objectives: Inhibition of the organic cation transporter-2 renal tubule transporter by dolutegravir leads to serum creatinine increase. Serum cystatin C is a non-organic cation transporter-2-dependent marker, possibly enabling glomerular filtration rate (GFR) estimation under dolutegravir. Our goal was to evaluate the changes in creatinine- and cystatin C-based estimated GFR values before and after dolutegravir initiation. Methods: Creatinine and cystatin measurements were carried out on frozen plasma samples from HIV-1-infected patients, before and after dolutegravir initiation, between October 2016 and March 2017 at Pitié-Salpêtrière Hospital. CKD-EPI equations were used to estimate mean GFR from creatinine and cystatin C values. Variations were analysed by paired t -test. Results: Forty-four patients were included [median age = 48 years (IQR 36–58) and median CD4 count = 592 cells/mm 3 (IQR 388–728)], including 6 ART-naive patients and 38 on switch strategies [72% with viral load <50 copies/mL and median ART duration = 13 years (IQR 5–20)]. Before dolutegravir initiation (median time = 41 days), 19 patients (43%) had creatinine-based estimated GFR <90 mL/min/1.73 m 2 and 11 (25%) had cystatin C-based estimated GFR <90 mL/min/1.73 m 2 . After dolutegravir initiation, serum creatinine values significantly increased (+8.6 μmol/L, 95% CI +5.8; +11.4, P < 0.001) and associated estimated GFR significantly decreased (−7.7 mL/min/1.73 m 2, 95% CI −10.4; −5.1, P < 0.001). In contrast, there was no significant change in cystatin C value variation and associated estimated GFR. The same results were observed regardless of renal function at baseline. Conclusions: Creatinine values increased after dolutegravir initiation, whereas no change was observed for cystatin C values. Use of cystatin C may enable better understanding of plasma creatinine fluctuations after dolutegravir initiation, particularly in high-risk renal patients.